2004
DOI: 10.1128/jcm.42.6.2783-2785.2004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance and Mechanism of Gas Formation of Pyogenic Liver Abscess Due toKlebsiella pneumoniae

Abstract: We enrolled 22 patients with gas-forming pyogenic liver abscess in a study to assess the mechanism of gas formation. Klebsiella pneumoniae was cultured from specimens from all patients. Gas and pus samples from abscesses revealed four major components: nitrogen, oxygen, carbon dioxide, and hydrogen; this implicates mixed acid fermentation of glucose as the mechanism of gas formation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
107
2
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 18 publications
3
107
2
2
Order By: Relevance
“…K. pneumoniae is the most common pathogen responsible for the disease, whereas Salmonella-related GFPLA is uncommon (28,29). GFPLA is a condition characterized by the vigorous metabolism and growth of bacteria, and it is closely associated with diabetes mellitus (28). The present patient did not have diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…K. pneumoniae is the most common pathogen responsible for the disease, whereas Salmonella-related GFPLA is uncommon (28,29). GFPLA is a condition characterized by the vigorous metabolism and growth of bacteria, and it is closely associated with diabetes mellitus (28). The present patient did not have diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Gasforming microorganisms produce formic hydrogenlyase, which converts formic acid to CO2 and H2. Accumulation is due to the increased production of gas, impaired transportation of gas, and equilibration between gases in the local tissue and the abscess (28,29). No evidence of gas accumulation was seen on the admission MDCT scan or X-ray in the present case, suggesting that gas formation began after admission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gas-forming pyogenic liver abscess (GFPLA) is even rarer, which accounts for 7% to 24% of PLA 4 . It is reported that GFPLA only accounted for less than 4% of all PLA over an eight-year period in a local hospital of Brunei 2 .…”
mentioning
confidence: 99%
“…K. pneumoniae has been emerging as the most common pathogen of PLA in the Asian population, especially GFPLA 4,6 . A clinical study revealed that K. pneumoniae was isolated from pus in all patients who had GFPLA except two ones 4 . Besides Klebsiella spp., other organisms were reported to cause GFPLA including Escherichia spp., Salmonella spp.…”
mentioning
confidence: 99%